2006
DOI: 10.15517/rbt.v54i4.3098
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de hojas por herbívoros en manglares del estuario del Río Dagua, Costa Pacífica Colombiana

Abstract: Leaf consumption by herbivores in mangroves of the Dagua river estuary, Pacific coast of Colombia. Herbivore leaf consumption of various mangrove species in relation to environmental factors and leaf hardness were studied in the Dagua river estuary, Colombia. Leaf consumption and damage were assessed by measuring the percentage of area attacked by herbivores, distinguishing between consumption and damage. The species that suffered the highest consumption, such as Avicennia germinans (Avicenniaceae) and Laguncu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Data obtained for herbivory show important differences when comparing seedlings (0%–100% range) with trees (0%–64% range), but the overall average damage value of 10.2% (±25.4 SD ) of the total leaf area is similar to leaf herbivory estimations reporting around 10% damage (Brauko et al, 2011; Cannicci et al, 2008; Duke, 2002; Erickson et al, 2012; Faraco & Lana, 2004; Farnsworth & Ellison, 1991; Feller, 2002; Johnstone, 1981; Menezes & Piexoto, 2009; Robertson, 1991; Robertson & Duke, 1987; Romero et al, 2006; Sousa & Dangremond, 2011). These results in herbivory damage were obtained under different environmental conditions, population dynamics, leaf chemistry, nutritional value, and palatability (Duke, 2002; Faraco & Lana, 2004; Farnsworth & Ellison, 1991; Feller et al, 2013; Fernandes et al, 2009; Kihia et al, 2012; Lacerda et al, 1986; Ohsaki et al, 2020; Onuf et al, 1977; Sato, 2018; Saur et al, 1999; Tong et al, 2006) and by discrete or continuous measurement methods (Cannicci et al, 2008; Menezes & Piexoto, 2009; Silva et al, 2015; Sousa & Dangremond, 2011).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Data obtained for herbivory show important differences when comparing seedlings (0%–100% range) with trees (0%–64% range), but the overall average damage value of 10.2% (±25.4 SD ) of the total leaf area is similar to leaf herbivory estimations reporting around 10% damage (Brauko et al, 2011; Cannicci et al, 2008; Duke, 2002; Erickson et al, 2012; Faraco & Lana, 2004; Farnsworth & Ellison, 1991; Feller, 2002; Johnstone, 1981; Menezes & Piexoto, 2009; Robertson, 1991; Robertson & Duke, 1987; Romero et al, 2006; Sousa & Dangremond, 2011). These results in herbivory damage were obtained under different environmental conditions, population dynamics, leaf chemistry, nutritional value, and palatability (Duke, 2002; Faraco & Lana, 2004; Farnsworth & Ellison, 1991; Feller et al, 2013; Fernandes et al, 2009; Kihia et al, 2012; Lacerda et al, 1986; Ohsaki et al, 2020; Onuf et al, 1977; Sato, 2018; Saur et al, 1999; Tong et al, 2006) and by discrete or continuous measurement methods (Cannicci et al, 2008; Menezes & Piexoto, 2009; Silva et al, 2015; Sousa & Dangremond, 2011).…”
Section: Discussionsupporting
confidence: 81%
“…This preference for seedlings may be explained by tender leaves with higher nutritive value in young plants and fewer secondary compounds. As leaves mature, the nutrient content declines, excreted salts accumulate on the surface, and leaf toughness increases with metabolic changes in internal fluxes of carbon and minerals (Balakrishnan et al, 2016; Choong, 1996; Elster et al, 1999; Faraco & Lana, 2004; Farnsworth & Ellison, 1991; Ohsaki et al, 2020; Robertson & Duke, 1987; Romero et al, 2006; Roth‐Nebelsick et al, 2001; Saur et al, 1999; Silva et al, 2015; Tiffin, 2002). In another study, Farnsworth and Ellison (1991) found variations in damage between trees and seedlings in Neotropical mangroves (Belize), with higher percentages sometimes occurring in trees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some micronutrients (e.g., Fe, Mg, Ca) may be more available to introduced mangroves (Appendix S2: Table S1) and enhance mangrove growth in some contexts (Reef et al, 2010), but is unlikely to explain performance and damage differences alone. Furthermore, we do not think such differences are driven by inherent differences in consumer diversity and abundance between the Pacific and Caribbean basins because Eastern Pacific mangroves also host similar enemies and damage levels as the Caribbean (Dangremond, 2015; Farnsworth & Ellison, 1997; Perry, 1988; Romero et al, 2006). Similarly, our results may partially stem from differences in island vs. mainland sites.…”
Section: Discussionmentioning
confidence: 96%